Steel Corrosion Protection with Water-Soluble Chitosan Inhibitor in 0,1 M HCl Solution Media - Fitria, Reffy Ika; Mahatmanti, F. Widhi; Kurniawan, Cepi; Kusumastuti, Ella (Indonesian Journal of Chemical Science, 2021)
Corrosion in steel can reduce the steel quality, so it is necessary to have a corrosion inhibitor. Water-soluble chitosan can be an alternative as corrosion inhibitors. This study aims to determine the efficiency of water-soluble chitosan inhibitor (WSC) added to the corrosive HCl solution in the steel protection process, and to determine the maximum concentration of WSC as a steel corrosion protector. Water-soluble chitosan (WSC) has been prepared from chitosan by reacting with H2O2. The products obtained were used as corrosion protection inhibitors in steel in a corrosive solution of 0,1 M HCl. Chitosan and WSC were characterized by their physical properties and functional groups using FTIR and physical tests for yield, viscosity, molecular weight (BM),% DD, solubility, and water content. . The effectiveness of WSC in corrosion protection of steel in corrosive 0,1 M HCl solution was studied by weight loss and potentiodynamic polarization methods. The results obtained by chitosan were a viscosity of 1,4969 cP, BM 8,38 x 104,% DD 77,17%, 10,25% moisture content and 33,48% solubility. Water-soluble chitosan obtained yield 86.325%, viscosity 0,296 cP, BM 6,9 x 103,% DD 79,95%, water content 27,07% and 72,77% solubility. Inhibitor efficiency was found in WSC 2000 ppm and 0,1 M HCl, which was 68,15% EI (weight loss), while the potentiodynamic polarization method obtained an EI of 87,5%.